2010
DOI: 10.1111/j.1570-7458.2010.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg hatching response to a range of air humidities for six species of predatory mites

Abstract: The efficiency of biological control agents is often affected by local conditions such as low relative humidity (r.h.). This is especially true for mites of the family Phytoseiidae, and particularly for their egg stage. A key issue in biological control is thus to assess the drought tolerance of phytoseiid species that are (or that will be) commercialized. In this study, we evaluated the egg hatching response to a humidity range for six species of Phytoseiidae, by assessing the relative air humidity and vapour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
0
25
0
7
Order By: Relevance
“…La HR 50 es a menudo discutida debido a su relación directa con la humedad relativa ambiental, en cambio la VPD 50 es dependiente de la temperatura, lo que permite comparaciones estandarizadas (Ferrero et al, 2010).…”
Section: Análisis Estadísticounclassified
See 2 more Smart Citations
“…La HR 50 es a menudo discutida debido a su relación directa con la humedad relativa ambiental, en cambio la VPD 50 es dependiente de la temperatura, lo que permite comparaciones estandarizadas (Ferrero et al, 2010).…”
Section: Análisis Estadísticounclassified
“…Uno de estos factores, la humedad relativa, afecta directamente sobre la supervivencia de los huevos de los fitoseidos (Walzer et al, 2007;Ghazi y Amano, 2016). Es un gran desafío encontrar depredadores tolerantes a la baja humedad relativa, especialmente para los cultivos donde la humedad es a menudo por debajo del 50-60%, lo que ha sido considerado como un límite para el desarrollo de muchos de los ácaros depredadores (Ferrero et al, 2010). En los estudios biológicos, las condiciones del vapor de agua se expresan comúnmente como humedad relativa (HR; %), que es el porcentaje de la presión de vapor [PV; Pa (Pascales)] en la presión de vapor saturada (PVS; Pa) a una temperatura del aire, o como un déficit de la presión de vapor (DPV; Pa) que es la diferencia entre PVS y PV.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Amblyseius swirskii are considered a drought sensitive mite species, as egg hatching for mites is largely related to humidity levels, with a higher egg hatch rate in more humid conditions (Ferrero et al, 2010). Humidity levels can interact with temperature to affect the level of efficacy of natural enemies in greenhouses (Heinz et al, 2004).…”
Section: Humidity and Vapor Pressure Deficitmentioning
confidence: 99%
“…They suggested that this success was due to increased juvenile survival and development rate when provided a mixed diet. As this mite originates from the Mediterranean basin, mostly found in humid coastal areas, A. swirskii prefer high temperatures and have a critical RH limit of ~70%, anything lower may cause their eggs to desiccate (de Moraes et al, 2004;Ferrero et al, 2010;Porath & Swirski, 1965). Buitenhuis et al (2010a) recently discovered that A. swirskii does not disperse well when applied to separated plants.…”
Section: Acari (Mites)mentioning
confidence: 99%